Modified nanoporous membranes on centrifugal microfluidic platforms for detecting heavy metal ions. (May 2014) - Chang, H.-C.; Chen, Y.-H.; Lo, A.-T.; Hung, S.-S.; Lin, S.-L.; Chang, I.-N.; Lin, J.-C.
Abstract : The modified nanoporous membranes on centrifugal microfluidic platforms are developed for detecting heavy metal ions with high selectivity. The nanomaterials of polyrhodanine, activated alumina and activated carbon are deposited on nanoporous anodic aluminium oxide (AAO) membranes for enhancing filtration to remove ions of lead (Pb(II)), arsenic (As(III)) and cadmium (Cd(II)) from aqueous solution. By detecting chemiluminescence (CL) reaction, the concentrations of heavy metal ions can be obtained. A pneumatic-and-centrifugal microfluidic detection system was used to perform microfluid separation and CL detection for measuring selected ions concentration. The removal efficiency of 92, 82 and 78% were observed for Pb(II), As(III) and Cd(II) ions, respectively. The removal rate is performed up to 70% for mixed ions filtration by a sequence of multi-modified AAO membranes. The modified nanofiltration films on microfluid platform have potential applications in removing heavy metal ions from water, soil, food and drug.